ANALISIS RISIKO PADA PELAKSANAAN PROYEK PEMBANGUNAN SARANA PENGENDALIAN BANJIR PADA WADUK MUARA NUSA DUA DENPASAR - WANGSA, ANAK AGUNG RATU RITAKA; PRAGANINGRUM, TJOKORDA ISTRI; LESTARI, I GUSTI AGUNG AYU ISTRI; SURYATMAJA, IDA BAGUS (Universitas Mahasaraswati K. Mataram, 2023)
Flooding that occurs due to runoff and scouring of Nusa Dua estuary reservoir water in Denpasar city causes the risk of inundating the surrounding roads and entering the mangrove forest. One of the efforts made by the Bali-Penida River Basin Hall is to carry out a flood control facility construction project. The purpose of this study is to identify the risks faced, measure and determine the magnitude of acceptable risks. The method used is descriptive with a qualitative approach. Data collection was conducted by interviews related to risk identification and questionnaires related to risk assessment. The results showed that the risks identified in the implementation of the flood control facility development project in the Nusa Dua estuary reservoir amounted to 36 risks consisting of 10 risk sources. The dominant source of risk is technical, project and safety risks with a percentage of 14%. After an assessment by 17 respondents, there were 15 risks (86%) with unacceptable categories, 10 risks (63%) with undesirable categories, 7 risks (38%) with acceptable categories, and 4 risks (13%) with negligible categories.